Eukaryotic mRNA Decapping Activation - Vidya, Elva; Duchaine, Thomas F. (Frontiers in Genetics, 2022)
The 5’-terminal cap is a fundamental determinant of eukaryotic gene expression which facilitates cap-dependent translation and protects mRNAs from exonucleolytic degradation. Enzyme-directed hydrolysis of the cap (decapping) decisively affects mRNA expression and turnover, and is a heavily regulated event. Following the identification of decapping holoenzyme (Dcp1/2) over two decades ago, numerous studies revealed the complexity of decapping regulation across species and cell types. A conserved set of Dcp1/2-associated proteins, implicated in decapping activation and molecular scaffolding, were identified through genetic and molecular interaction studies, and yet their exact mechanisms of action is only emerging. In this review, we discuss the prevailing models on the roles and assembly of decapping co-factors, with considerations of conservation across species and comparison across physiological contexts. We next discuss the functional convergences of decapping machineries with other RNA-protein complexes in cytoplasmic P bodies and compare current views on their impact on mRNA stability and translation. Lastly, we review the current models of decapping activation and highlight gaps in our current understanding.